Initiation of Apoptosis by Granzyme B Requires Direct Cleavage of Bid, but Not Direct Granzyme B–Mediated Caspase Activation - Sutton, Vivien R. (The Rockefeller University Press, 2000)
The essential upstream steps in granzyme B–mediated apoptosis remain undefined. Herein, we show that granzyme B triggers the mitochondrial apoptotic pathway through direct cleavage of Bid; however, cleavage of procaspases was stalled when mitochondrial disruption was blocked by Bcl-2. The sensitivity of granzyme B–resistant Bcl-2–overexpressing FDC-P1 cells was restored by coexpression of wild-type Bid, or Bid with a mutation of its caspase-8 cleavage site, and both types of Bid were cleaved. However, Bid with a mutated granzyme B cleavage site remained intact and did not restore apoptosis. Bid with a mutation preventing its interaction with Bcl-2 was cleaved but also failed to restore apoptosis. Rapid Bid cleavage by granzyme B (<2 min) was not delayed by Bcl-2 overexpression. These results clearly placed Bid cleavage upstream of mitochondrial Bcl-2. In granzyme B–treated Jurkat cells, endogenous Bid cleavage and loss of mitochondrial membrane depolarization occurred despite caspase inactivation with z-Val-Ala-Asp-fluoromethylketone or Asp-Glu-Val-Asp-fluoromethylketone. Initial partial processing of procaspase-3 and -8 was observed irrespective of Bcl-2 overexpression; however, later processing was completely abolished by Bcl-2. Overall, our results indicate that mitochondrial perturbation by Bid is necessary to achieve a lethal threshold of caspase activity and cell death due to granzyme B.